Health Shocks, Workforce Resilience, and Economic Productivity: Longitudinal Evidence from East Java - Febrian, Febrian; Ihlasuddini, Habiba Nabila; Akbar, Muh. Imaduddin (Jurnal Ekonomika : INDEPENDEN, 2025)
This study investigates the relationship between health status, health shocks, and labor force participation in East Java using panel data from the Indonesia Family Life Survey (IFLS) waves 3, 4, and 5. Employing fixed-effects and random-effects logistic regression models, the results show that good self-reported health significantly increases the probability of labor force participation, affirming the economic value of health as human capital. However, health shocks—captured as changes in health condition between waves—do not significantly predict labor market disengagement, indicating possible measurement limitations or labor supply rigidity. The analysis further reveals that the positive effect of good health is substantially weaker for women, suggesting gendered constraints in labor returns to health. Educational attainment consistently predicts labor force participation, reinforcing the complementary role of formal education in economic resilience. These findings contribute to the growing empirical literature on the health–labor nexus in emerging regional economies.